Oracle database 11g & MySQL 5.6 developer handbook - McLaughlin, Michael [ (Michael J.)] (McGraw-Hill, 2012)
This oracle press guide is the definitive reference to programming and working with oracle database 11g and oracle MySQL in a mixed environment